Transformasi Visual Tokoh Mahabharata dalam Sejarah Komik Indonesia - Sunarto, Wagiono (PANGGUNG, 2013)
ABSTRACTÂ The great epic of Mahabharata was created through a long period of time in the eastern Punyab region, India. The process of writing was initiated around 300 BC, and in 7 centuries the book was developed by many generations of writers until the final stage which consists of about 10.000 celokas in 18 parwas. After initial stages of development, the great epic continued to spread to other counÂ tries and regions, especially to cultures which were influenced by Hinduâs or Budhaâs civilization, including Indonesia (Java, Bali, Lombok, and other regions). In Indonesia, the story was rewriten, reinterpreted and readapted over and over into many spreading cultures and eventually transformed into many forms of visual and performing arts. The long proccess of construction and reconstraction of the story and the characters was a very interesting cultural proccess which is still in progress in our time. The phenomena could be observed in the adaption of the story in the history of Indonesian Comic Books, particullary in the transformation of visual styles in some of modern comic book examÂ ples. This visual transformation reflects the change of cultural values and communication circumÂ stances in particular time of history, which in turn change the worldâs view of the creator in respons to, and relevant with the value changes of the society.Â Keywords: Visual transformation, Indonesian comic historyÂ Â Â ABSTRAKÂ Epik Â besarÂ  Mahabharata tercipta melalui jangka waktu yang Â panjang di Â bagianÂ  timur wilayah Punyab, India. Proses penulisannya dimulai sekitar 300 SM, dan selama 7 abad buku tersebut dikembangkan oleh berbagai generasi penulis sampai pada tahap akhir yang terdiri atas sekitar 10.000 celoka dalam 18 parwa. Setelah tahap awal pengembangannya, epik besar tersebut terus menyebar ke negara-negara dan daerah-daerah lain, khususnya ke masyarakat yang dipengaruhi oleh kebudayaan Hindu atau Budha, termasuk Indone- sia (Jawa, Bali, Lombok, dan daerah lainnya). Di Indonesia, cerita tersebut ditulis ulang, ditafsirkan dan diadaptasi kembali ke berbagai budaya dan akhirnya ditransformasikan ke dalam berbagai bentuk seni visual dan pertunjukan. Proses konstruksi dan rekonstruksi yang panjang dari cerita dan karakter itu merupakan proses budaya yang sangat menarik yang masih berlangsung hingga masa kini. Fenomenanya dapat diamati melalui adaptasi dari kisah dalam sejarah Buku Komik Indonesia, khususnya pada transformasi gaya visual dalam beberapa contoh buku komik modern. Transformasi visual ini mencerminkan per- ubahan nilai-nilai budaya dan suasana komunikasi pada waktu tertentu dalam sejarah, yang pada gilirannya mengubah cara pandang respon kreator, serta relevan dengan per- ubahan nilai-nilai masyarakat.Â Kata kunci: transformasi visual, sejarah komik Indonesia